Clinical toxicology in Edinburgh, two centuries of progress. (July 2013) - Proudfoot, Alex T.; Good, Alison M.; Bateman, D. Nicholas
Abstract The Scottish Poisons Information Bureau was established in Edinburgh in September 1963 and shortly afterwards one of the wards of the city's Royal Infirmary was designated a Regional Poisoning Treatment Centre. Both units were soon to be brought under one roof. To mark this 50th anniversary, we review how they built upon a history dating from the early 19th century and highlight their influence on current clinical toxicological practice and the delivery of poisons information. While many centres worldwide seek to improve the care of poisoned patients, the contribution of Edinburgh over the past 50 years has been notable.